Meningkatkan Kemampuan Tajwid Remaja melalui Magrib Mengaji di Dusun Cikuya, Desa Selajambe, Kabupaten Kuningan - Novianingsih, Anes (Khidmat, 2021)
Tajweed can be interpreted as reading the Qur'an by fulfilling the rights of each letter, both in terms of makhraj or its nature, fulfilling the rights of every reading law arising from the meeting of the letters and also fulfilling other rules that apply in recitations of the Qur'an. The purpose of this study was to improve the recitation ability of junior high school students through the evening prayer in Cikuya Hamlet, Selajambe Village, Kuningan Regency. Data collection techniques in this study are (a) observation, which is a way of collecting data by conducting direct observations on learning activities on the object under study; and (b) documentation is a way to collect data which includes sound recordings and photographs related to the research problem. In the application of this tajwid science, researchers provide material to children, then they are recorded, read together repeatedly and memorized and applied in reading the Qur'an. In the application of recitation through maghrib, this Koran has been programmed by the Governor of West Java which aims to improve the quality of children's worship in West Java.